HUBUNGAN KEMAMPUAN MENGGAMBAR FREE BODY DIAGRAMS DENGAN KEMAMPUAN KOGNITIF SISWA PADA MATERI KESEIMBANGAN DAN DINAMIKA ROTASI - Mirna Syafitri; Zulirfan Zulirfan; Yennita Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The aim of this study is to determine the relationship of the ability in drawing free body diagrams with cognitive ability of students on balance and dynamic rotation materials. Correlational study was used as research method, the ability to draw free body diagrams was defined as independent variable while dependent variable was students’ cognitive ability. Primer data was obtained directly from the sample by using the ability of drawing free body diagram and cognitive ability students test instruments. Coefficient of correlation between those variables was 0.656, it can be catagorized in high level. According to regression analysis, the coefficient of regression was +3,682, means that independent and dependent variable have a positive relation. Coefficient of determination was 43%, it showed that the contribution of the ability in drawing free body diagrams to cognitive ability students is 43%. Significancy test indicated that there was a significant influence between both of variables. Based on that, it can be concluded that there is a positive and significant relation between the ability in drawing free body diagrams and cognitive ability students on balance and dynamic rotation materials of senior high school physics subject.Keywords : Ability to draw free body diagrams, balance and dynamics rotation, cognitive ability, physics learning